2005
DOI: 10.1093/alcalc/agh180
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary Ethanol Intake Increases Extracellular Acetylcholine Levels in the Ventral Tegmental Area in the Rat

Abstract: The present results suggest that voluntary ethanol intake enhances extracellular ventral tegmental acetylcholine that may interact with nicotinic acetylcholine receptors, possibly alpha-conotoxin MII sensitive receptors, localized in the ventral tegmental area that subsequently may stimulate dopamine overflow in the nucleus accumbens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
96
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(100 citation statements)
references
References 65 publications
2
96
0
1
Order By: Relevance
“…Consistent with this observation, Landgren et al (2009) report an interesting association with CHRNA4 and obesity, particularly within heavy alcohol users. This result may not be surprising given that the cholinergic dopaminergic reward effect seen with alcohol can also be seen with food (Larsson et al, 2005). Associations between CHRNA4 and ADHD (Todd et al, 2002) and cognitive attention (Greenwood et al, 2012), may suggest yet other mechanisms underlying the relationship between CHRNA4 and frequency of binging.…”
Section: Discussionmentioning
confidence: 93%
“…Consistent with this observation, Landgren et al (2009) report an interesting association with CHRNA4 and obesity, particularly within heavy alcohol users. This result may not be surprising given that the cholinergic dopaminergic reward effect seen with alcohol can also be seen with food (Larsson et al, 2005). Associations between CHRNA4 and ADHD (Todd et al, 2002) and cognitive attention (Greenwood et al, 2012), may suggest yet other mechanisms underlying the relationship between CHRNA4 and frequency of binging.…”
Section: Discussionmentioning
confidence: 93%
“…This reward link is activated by natural as well as chemical reinforcers, as reviewed previously (Larsson and Engel 2004). Involvement of this reward link in druginduced as well as natural reward has been implied, thus food as well as alcohol intake increases the ventral tegmental acetylcholine levels as well as accumbal dopamine levels (Hernandez and Hoebel 1988;Larsson et al 2005;Rada et al 2000). GHS-R1A is expressed in the LDTg (Guan et al 1997), specifically on cholinergic cells , suggesting that ghrelin may have direct effects in this reward node.…”
Section: The Central Ghrelin Signalling System Integrates With a Key mentioning
confidence: 85%
“…These data are verified in clinical tests; thus blocking these subtypes, by using varenicline, reduces the intake of alcohol in heavy drinking smokers (McKee et al 2009) and one haplotype of the 6* gene is associated with heavy alcohol use ). Furthermore, it has been shown that excessive alcohol intake in rats consuming alcohol for a long period of time causes a release of acetylcholine in the VTA followed by an increase in accumbal dopamine levels, showing that alcohol like ghrelin activates the cholinergicdopaminergic reward link (Larsson et al 2005). Taken together, there appears to be neurochemical analogies and overlaps between ghrelin and alcohol, where the cholinergic-dopaminergic reward link is the common denominator.…”
Section: The Central Ghrelin Signalling System Integrates With a Key mentioning
confidence: 96%
“…Alcohol targets components of the mesolimbic dopamine system (Larsson & Engel 2004;Vengeliene et al 2008;Soderpalm, Lof, & Ericson 2009), which is involved in the expression of its reinforcing properties (Adinoff 2004). Beyond the mesolimbic dopamine system, which includes dopamine projections from the ventral tegmental area (VTA) to nucleus accumbens (NAc) (Koob & Bloom 1988;Kelley & Berridge 2002), recent studies show that alcohol activates the cholinergic inputs from the laterodorsal tegmental nucleus (LDTg) (Larsson et al 2005).…”
Section: Introductionmentioning
confidence: 99%